2022
DOI: 10.3390/app12063057
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinusitis of Odontogenic Origin: Prevalence among 3D Imaging—A Retrospective Study

Abstract: The aim of this study was to investigate the prevalence of maxillary sinus mucosal thickening and compare it to the presence of odontogenic pathology of adjacent teeth. Three hundred and twenty-one full maxilla cone-beam computed tomography scans were examined. The parameters investigated included signs of maxillary sinus mucosal thickening and the diagnosis and proximity of the adjacent teeth. Statistical analysis was conducted using IBM SPSS version-16.0 (SPSS Inc., Chicago, IL, USA). Out of the 2001 teeth e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Kuligowski et al reported a prevalence of up to 40 % for odontogenic sinusitis, while Al-Ehmeli et al, found a 37.21 % overall prevalence of sinus pathology in their patient cohort ( Kuligowski et al, 2021 , Al-Ehmeli, 2015 ). In contrast, Mahasneh et al observed a notably higher prevalence, with 76.1 % of patients showing incidental pathological findings ( Mahasneh et al,. 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…Kuligowski et al reported a prevalence of up to 40 % for odontogenic sinusitis, while Al-Ehmeli et al, found a 37.21 % overall prevalence of sinus pathology in their patient cohort ( Kuligowski et al, 2021 , Al-Ehmeli, 2015 ). In contrast, Mahasneh et al observed a notably higher prevalence, with 76.1 % of patients showing incidental pathological findings ( Mahasneh et al,. 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…Vallo et al [8] reported that pathologies were more common in the left maxillary sinus. On the other hand, Mahasneh et al [4] reported that the incidence of MT was higher in the right maxillary sinus and determined that this difference might be the result of septum deviation affected by the presence of concha bullosa. When dental pathologies and other factors are taken into account, it has been reported by studies that an increase in MT may occur in the maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory changes in the maxillary sinus mucosa are thought to occur in this way. [15] Mahasneh et al [4] reported that 54% of teeth with PL caused an increase in MT in the adjacent maxillary sinus, and this rate increased 2.52 times in the presence of PL. Lu et al [3] reported that the amount of MK was significantly associated with the increase in the size of the periapical lesion and the number of teeth with the periapical lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Saibene et al, Dobroy and Zarzecka, and Kim et al (36)(37)(38), computed tomography (CT) and cone beam CT (CBCT) are the most commonly used tools to diagnose sinusitis and identify the dental problem. The study of the maxillofacial region has been revolutionized with the use of high-resolution multiplanar CBCT (39,40), which is why cone bean tomography has been used for the evaluation of paranasal sinuses in order that the vision in both the axial and coronal angles allows us to observe the maxillary sinus in relation to some periapical pathology or a sinus floor defect (1,41). Oleg et al, Goyal et al, Kim et al (42)(43)(44) stated in their study that the principal radiographic signs of odontogenic sinusitis were: thickened mucosa, unilateral maxillary sinus opacification, with or without other sinus involvement, and presence of fluid levels.…”
Section: Marta Kwiatkowsk Et Al Cristian Martu Et Al and Allevi Et Almentioning
confidence: 99%